1999
DOI: 10.1038/sj.jhh.1000719
|View full text |Cite
|
Sign up to set email alerts
|

Target organ involvement in hypertensive patients in Eastern Sudan

Abstract: Hypertension has become a major cause of cardiovascular morbidity and mortality in both the developed and the developing nations. In a cross-sectional study we assessed the state of blood pressure (BP) control and the pattern of target organ complications in 198 Sudanese patients treated in a teaching hospital in Kassala town in Eastern Sudan, (mean age 53 years, 76% women). Excellent BP control (BP Ͻ140/90 mm Hg) was achieved in 46% of the patients. Stage 2 or Stage 3 target organ involvement, particularly al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
1
7
1
Order By: Relevance
“…Similarly, Cui et al, Ayodele et al, Addo et al, and Hussain et al, found that older age was a risk factor for end organ damage in hypertension. 14,16,21,23 In present study there was no association between gender and EOD (p= 0.43). Similar findings were reported in a Nigerian study by Ayodele et al, in treated hypertensives.…”
Section: Discussioncontrasting
confidence: 54%
“…Similarly, Cui et al, Ayodele et al, Addo et al, and Hussain et al, found that older age was a risk factor for end organ damage in hypertension. 14,16,21,23 In present study there was no association between gender and EOD (p= 0.43). Similar findings were reported in a Nigerian study by Ayodele et al, in treated hypertensives.…”
Section: Discussioncontrasting
confidence: 54%
“…This perhaps, only reflects the population/gender distribution of the workers in IITA as previous reports have found female preponderance in keeping with the notion that hypertension is more common in females in middle age (3,5). Whereas some studies have noted that younger hypertensive patients are more likely to miss there medications leading to poor control(6,7), our findings here suggest otherwise, as the mean age of patients who were fully controlled in this study was significantly lower than those that were not controlled at all.…”
Section: Discussionmentioning
confidence: 65%
“…It is a major cause of morbidity and mortality, and a leading cause of stroke, heart and kidney disease even in the developed world (1,2). Analysis of levels of blood pressure control has shown that optimal blood pressure control ranged between 21% and 53% in some studies (3). These figures were mostly from studies where patients procure drugs by themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of awareness is very significant in the prevalence of HTN and uncontrolled high BP 10,16. More attention must be given to HTN as it is a common risk factor for stroke29 and kidney disease,30 which are recognised to be rapidly increasing in Sudan.…”
Section: Discussionmentioning
confidence: 99%